Metafora Konseptual Buku dalam Masyarakat Indonesia - Diana Sri Suryani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is a cognitive linguistic study of conceptual metaphors of books in Indonesian society. The aim is to get a better understanding of the use of conceptual metaphors of books in Indonesian society, so that the conceptualization of books can be identified. This research is a descriptive qualitative research. The data collection method used is the listening method with reading and recording techniques. Data were obtained through posts and tweets in the #HariBukuNasional and Literary Base accounts on Twitter and Instagram. The data were analyzed using the conceptual metaphor theory proposed by Lakoff & Johnson. The results show that Indonesians use a variety of conceptual metaphors to conceptualize books, such as books are love; books are family; books are friends; books are travel; books are solutions; books are windows of the world; books are nutrition; books are home; books are the ocean of science; and books are sources of happiness. These findings reflect the significance of books in various aspects of Indonesian life and indicate that books have positive connotations in the perceptions of Indonesians